Aspects of Enterovirus Infection Molecular Epidemiology in Sakhalin Region (during years 2016–2018) - E. Yu. Sapega; L. V. Butakova; O. E. Trotsenko; O. A. Funtusova; G. P. Kovtoniuk (Эпидемиология и вакцинопрофилактика)
Relevance.  Annual elevation of enterovirus infection (EVI) incidence in the Russian Federation  as well as in the Sakhalin region determine  a necessity  of continuous  surveillance  involving molecular-genetic  methods  and  phylogenetic  analysis.  Objective:  to highlight epidemiological and molecular-genetic  peculiarities of EVI in the Sakhalin region during 2016-2018 years. Materials and methods.  Analysis of enterovirus incidence were based on official statistical reporting forms. The structure of enterovirus types was evaluated by means of molecular methods and followed by phylogenetic analysis. Results and discussion. A deterioration of epidemic situation concerning EVI that began in 2016 in the Sakhalin region included elevation of incidence and registration of enterovirus outbreaks in childcare facilities triggered by introduction of new enterovirus types or those that were not circulating for a long time suchas Coxsackievirus A-6, Coxsackievirus A-10, Coxsackievirus A-16, ECHO-9. The phylogenetic analysis of Coxsackievirus A-16 detected in the Sakhalin region revealed their similarities with two genovariants of B genogroup (В1а и В1b) that were continuously circulating in Russia and China. In addition, enterovirus ECHO-9 that was also circulating in other constituent entities of the Russian Federation was isolated in Sakhalin region from patients suffering from viral meningitis including two children from two different infection cites of EVI group incidence. Conclusion. An unfavorable epidemic situation concerning EVI was revealed in the Sakhalin region during the last three years of surveillance. It was caused by introduction and further spread among population of Coxsackieviruses A-6, 10, 16 and ECHO-9 that presumably have Russian or foreign origin.